Public Opinion and Political Philosophy: The Relation between Social-Scientific and Philosophical Analyses of Distributive Justice - Swift, Adam (1999)
This paper considers the relation between philosophical discussions of, and social-scientific research into popular beliefs about, distributive justice. The first part sets out the differences and tensions between the two perspectives, identifying considerations which tend to lead adherents of each discipline to regard the other as irrelevant to its concerns. The second discusses four reasons why social scientists might benefit from philosophy: problems in identifying inconsistency, the fact that non-justice considerations might underlie distributive judgments, the way in which different principles of justice can yield the same concrete distributive judgments, and the ambiguity of key terms. The third part distinguishes and evaluates three versions of the claim that normative theorising about justice can profit from empirical research into public opinion: that its findings are food for thought, that they amount to feasibility constraints, and that they are constitutive of normatively justified principles of justice. The view that popular opinion about justice has a strongly constitutive role to play in justifying principles of distributive justice stricto sensu is rejected, but it is argued that what the people think (and what they can reasonably be expected to come to think) on distributive matters can be an important factor for the political theorist to take into account, for reasons of legitimacy, or feasibility, or both.
Keywords: Michael Walzer; Social Justice; John Rawls; Public Opinion; Distributive Justice; Desert